Molekularbiologie, Faunistik und Zoogeographie - Gerstmeier, Roland (Acta entomologica slovenica (Ljubljana), 2004)
Following a short description of the faunistics and zoogeography, four molecular biology methods (mtDNA, microsatellites, SSCP, RAPD) and their use in zoogeographical research are presented with examples.
Keywords: favna; molecular biology; molekularna biologija; zoogeografija